Determining Employee Productivity: Analysis of Competence, Organizational Commitment, Career Path, and Motivation - Faisal, Ahmad (Dinasti Publisher, 2025)
The purpose of this literature review is to develop hypotheses regarding the influence between variables that can be used for further research in the field of human resource management. The article “Literature Review on Employee Productivity Determinants: An Analysis of Competence, Organizational Commitment, Career Path, and Motivation” is a scientific literature article in the field of human resource management. The approach used in this literature review is descriptive qualitative. The data collection technique used is literature study or reviewing previous relevant articles. The data used in this descriptive qualitative approach were obtained from previous studies relevant to this study and sourced from academic online media such as Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar, and digital reference books. The results of this literature review article are as follows: 1) Competence influences employee productivity; 2) Organizational commitment influences employee productivity; 3) Career path influences employee productivity; and 4) Motivation influences employee productivity.